Analisis Tingkat Kepuasan Masyarakat Terhadap Kebijakan Tarif Tol Medan Tebing Tinggi - Fandy Rangkuty, Muhammad Hafif; Tarigan, Azhari Akmal (Universitas Labuhanbatu, 2021)
This study was conducted to evaluate the level of satisfaction of toll road users with regard to the tariffs set by the Government regarding the determination of the Medan - Tebing Tinggi Toll Road to the total volume of vehicles that pass. The research uses quantitative methods by applying survey techniques by distributing questionnaires. Sampling using purposive sampling technique with a sample of 150 respondents. Respondents' perceptions were measured using a Likert scale of 1-4. The Community Satisfaction Index (IKM) is calculated based on the PAN Ministerial Regulation Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey. The calculation results show that the IKM regarding the Medan-Tebing Tinggi toll tariff policy is 71.00 (included in the category B or Good value). This is because the service element that is considered good is Cost/Tariff compared to other service elements that get the highest interval value, namely 3.5 (Satisfied). So that the costs incurred to take the Medan-Tebing Tinggi toll road are considered affordable and still comparable to the distance traveled by the toll road. The recommendation in this study is that the government should further improve the quality of the roads, coupled with the number of uneven road connections.